Use clear messages to create a positive environment. (2nd January 2019) - Tassoni, Penny
Abstract : Penny Tassoni provides practical tips for helping children to cope with the demands of being in early years settings. When practitioners know a child well they can take a proactive approach to addressing situations where unwanted behaviours may occur.